The Importance of the Younger Generation in Combating the Dangers of Juvenile Delinquency: English - Anam Samsudin; Mislawi Yadi Adirasa (JOEY: Journal of English Ibrahimy, 2023)
This research explored the pivotal role of the younger generation in addressing the dangers associated with juvenile delinquency. The study examined the multifaceted benefits of involving youth in preventative and intervention strategies to curb delinquent behaviors. Through a comprehensive literature review and analysis, the research highlighted key findings. 1) Early intervention and prevention programs targeting at-risk youth offer a promising approach to disrupting the trajectory of delinquent behaviors. Engaging the younger generation through mentorship, education, and community involvement equips them with essential life skills and values that act as deterrents. 2)The influence of peers and positive role models plays a vital role in shaping behavior. 3) Empowering young individuals to take ownership of change promotes a sense of responsibility and agency. 4) The effective communication methods employed by the youth, such as social media, facilitate the dissemination of anti-delinquency messages. The research emphasized the long-term societal impact of involving the youth. By nurturing responsible, empathetic individuals, society sets the stage for sustained positive change, as engaged youth transition into responsible adults who contribute positively to their communities. Collaborative approaches that involve young individuals in understanding the root causes of delinquency led to more comprehensive solutions. The active involvement of the younger generation through early intervention, positive peer influence, empowerment, effective communication, and community collaboration not only addresses immediate challenges but also shapes a future defined by safer communities and responsible citizenship.